Youth Training Scheme, 1984 (London, 1984)
1984 1980-95 "Youth Training Scheme, 1984" [BW0208], 1984, Trades Union Congress The Youth Training Scheme (YTS) was an on-the-job training course for school leavers aged 16 and 17, managed by the Manpower Services Commission. The Scheme was brought into operation in 1983 by the Conservative Government to replace the Youth Opportunities Programme.